Filipino, isa kang alipin! - Garcia, Reynaldo Cruz (Parañaque Proverbs 1:7 Publishing House, 2004)
Social issues on the life of Filipinos.
Keywords: Philippines -- Social conditions -- 1986-.; Philippines -- Social policy -- 1986-.